(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Interest in alternative energy sources has been increased due to improved public awareness about the high energy cost and the adverse environmental impact of the conventional energy sources. This has caused a transition to a new market-based power network which, among other characteristics, allows more flexible incentives based demand-response-programs (DRP). Reliability aspects have been more challenging in remotely operated Independent-Microgrid-Networks (IMGN) mainly due to weather dependence. Such stochastic behavior has influenced the market prices of electricity and has created real time challenges for trade. The success of such uncertain energy systems depends to a large extent on new technical and financial tools. This requires to consider together the reliability and the financial cost–benefit analysis for every stakeholder of the deregulated electricity market. A novel decision making strategy for relating the system's reliability with cost-benefit incentives under IMGN paradigm has been proposed with an application of economic and signaling-game-theory (SGT).A relationship has been formulated with the consideration of maximizing the profit expectation of each player in the presence of the independent multi-generation resources with different penetration levels. This proposed model can be used as a tool for task scheduling problems and demand side management under the real time pricing schemes. The basic idea is to deal with the uncertainties involved to improve the reliability of renewable power systems. A simulation methodology for reliability evaluation and cost assessment in IMGN has also been developed. Results are discussed in comparison with the Time-of-Use (ToU) price rates.